Knowledge, attitude and behaviour around concussion at the FIFA Women`s World Cup 2023: part 2 - coaches, performance staff and players - Wilke, C. F.; Serner, A.; Massey, A.; McCall, A.; Fulcher, M.; Rosenbloom, C.; Carmody, S.; Patterson, S. D.; Okholm Kryger, K. (Science and Medicine in Football, 2025)
The objective of this observational cross-sectional study was to assess the knowledge, attitude and behaviour of coaches and performance staff (i.e. `coaching staff`), and players from the 32 teams qualified for the FIFA Women`s World Cup 2023 regarding assessment and management of concussion in football. Two online surveys were developed: 1) coaching staff, and 2) players. The results were analysed descriptively. Eighty-four coaching staff and 229 players completed the survey. Concussion knowledge: 39% of coaching staff and 33% of players were aware of concussion protocol(s). Knowledge: concussion symptom onset time was correctly reported by 18% of coaching staff and 11% of players. Knowledge about risks related to sustaining a concussion or returning to play too soon varied in both groups. Attitude: 26% of coaching staff and 31% of players reported being very confident or confident in recognizing a suspected concussion. Half of the players (52%) reported to always report symptoms of concussion if feeling any. One (1%) member of the coaching staff and 24 (10%) players reported feeling that a player can return to play with mild symptoms after a concussion. Behaviour: Most coaching staff reported they would have supportive behaviour if faced with a suspected concussion on the pitch. Among players, 64% stated that they would leave the assessment to their team`s medical staff, and 4% would encourage their teammates to keep playing. In conclusion, coaching staff and players showed limited knowledge about concussion. Most coaching staff reported attitudes and intended behaviour towards protecting players` health; whilst players' responses varied.